Implementasi Pelayanan Antar-Jemput Berbasis Aplikasi Transportasi Bajaj Online di Lingkungan Taman Kanak-Kanak - Cici Maisyaroh; Luthfi Acintya Kurniadewi; Fetty Ernawaty (Inovasi Pendidikan dan Anak Usia Dini, 2026)
This study aims to examine how an online bajaj-based pick-up and drop-off service developed by a kindergarten is implemented. The bajaj application is considered an innovation in a community-based educational transportation system. The limitations of conventional pick-up and drop-off systems in providing optimal efficiency, transparency, and safety form the basis of this research. This study employed a qualitative approach using a case study method, with data collected through observation, interviews, and documentation. The results indicate that the use of the online bajaj application improves service quality through features such as booking services, real-time location tracking,and notifications to parents, which enhance time efficiency, transparency, and a sense of security. Compared to commercial transportation services, the community-based service model allows for more controlled operational management. However, challenges such as low digital literacy among users, limited network infrastructure, and potential data security risks were also identified. Critically, this innovation contributes significantly to the development of the smart mobility concept in the education sector, although it still requires improvement in terms of system sustainability and user data protection.